Breast biopsy patterns and findings among older women undergoing screening mammography: The role of age and comorbidity. Issue 2 (March 2022) - Advani, Shailesh; Abraham, Linn; Buist, Diana S.M.; Kerlikowske, Karla; Miglioretti, Diana L.; Sprague, Brian L.; Henderson, Louise M.; Onega, Tracy; Schousboe, John T.; Demb, Joshua; Zhang, Dongyu; Walter, Louise C.; et al.
Abstract: Introduction: Limited evidence exists on the impact of age and comorbidity on biopsy rates and findings among older women. Materials and methods: We used data from 170, 657 women ages 66–94 enrolled in the United States Breast Cancer Surveillance Consortium (BCSC). We estimated one-year rates of biopsy by type (any, fine-needle aspiration (FNA), core or surgical) and yield of the most invasive biopsy finding (benign, ductal carcinoma in situ (DCIS) and invasive breast cancer) by age and comorbidity. Statistical significance was assessed using Wald statistics comparing coefficients estimated from logistic regression models adjusted for age, comorbidity, BCSC registry, and interaction between age and comorbidity. Results: Of 524, 860 screening mammograms, 9830 biopsies were performed following 7930 exams (1.5%) within one year, specifically 5589 core biopsies (1.1%), 3422 (0.7%) surgical biopsies and 819 FNAs (0.2%). Biopsy rates per 1000 screens decreased with age (66–74:15.7, 95%CI:14.8–16.8), 75–84:14.5(13.5–15.6), 85–94:13.2(11.3, 15.4), p trend  < 0.001) and increased with Charlson Comorbidity Score (CCS = 0:14.4 (13.5–15.3), CCS = 1:16.6 (15.2–18.1), CCS ≥2:19.0 (16.9–21.5), p trend  < 0.001).Biopsy rates increased with CCS at ages 66–74 and 75–84 but not 85–94. Core and surgical biopsy rates increased with CCS at ages 66–74 only. For each biopsy type, the yield of invasive breast cancer increased with age irrespective of comorbidity. Discussion: Women aged 66–84 with significant comorbidity in a breast cancer screening population had higher breast biopsy rates and similar rates of invasive breast cancer diagnosis than their counterparts with lower comorbidity. A considerable proportion of these diagnoses may represent overdiagnoses, given the high competing risk of death from non-breast-cancer causes among older women.